Profile of MIBI Liquid Phase Radiopharmaceutical for Myocardial Imaging - I. Daruwati; M.E. Sriyani; N.K. Oekar; A. Hanafiah; N. Zainuddin (PPIKSN-BATAN, 2016)
The 99mTc-MIBI radiopharmaceutical has been used innuclear medicine in Indonesia for myocardial imaging. BATAN researchers have mastered the technology to manufacture MIBI as a liophylized kit. A reformulation of MIBI radiopharmaceutical has been conducted to improve the stability of the kit especially in the liquid-phase kit. Basically, radiopharmaceuticals in liquid form are not different from the dry kit. However in the manufacturing of liquid-phase kit, lyophilization process was not done. To improve the stability of liquid kit, a reformulation of the components was conducted by using two separate vials (Formulation 2) and the characteristics were compared with the one-vial formulation (Formulation 1). The MIBI Formulation 2 consists of two vials, vial A containing 0.06 mg of SnCl2 2H2O and 2.6 mg Sodium Citrate 2H2O and vial B containing 0.5 mg of [Cu(MIBI)4]BF4, 1 mg of cysteine hydrochloride, and 20 mg of mannitol.The purposes of this study wereto determine the stability of two different formulations of MIBI as a liquid-phase kit, to compare their stability in different storage condition such as in refrigerator and freezer, and to compare the ratio of activities attained between target and nontarget organs after injection to animal model. As a diagnostic agent, MIBI was reconstituted with Technetium-99m as radionuclide tracer to 99mTc-MIBI labeled compound. The radiochemical purity of 99mTc-MIBI was determined by chromatography method using alumina thin-layer chromatography paper as the stationary phase and ethanol 95% as the mobile phase. The results showed MIBI Formulation 2 has a higher stability than Formulation 1. Formulation 2 also maintained a 96.68% radiochemical purity under 52-day storage and attained a target-to-nontarget activity ratio of 8.22.Received: 04 October 2014; Revised: 10 November 2015; Accepted: 25 November 2015